GAMBARAN UMUM TOKSOPLASMOSIS OKULER DI RUMAH SAKIT DR KARIADI SEMARANG: STUDI RETROSPEKTIF 5 TAHUN - Ariska, Amalia Dwi; Reki, Winarto; Novita, Dina (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2023)
Introduction: Ocular toxoplasmosis is the most common infectious etiology of posterior uveitis. The aim of this study is to describe the clinical characteristics of ocular toxoplasmosis in Dr. Kariadi Hospital, Semarang. Methods: A retrospective review of out-patient medical records of ocular toxoplasmosis at Dr. Kariadi Hospital Semarang from January 2018 to December 2022 was done. All toxoplasmic uveitis were included, whereas incomplete medical records and loss of follow-up were excluded. The clinical characteristics of patients were recorded and analyzed. Results: During 5 years a total of 160 patients were recruited of which 123 fulfilled the criteria, consisting of 47 males (38.2%) and 76 females (61.8%), mostly were acquired infection (97.6%) with immunocompetent status (75.6%), and affected unilateral eye (65%). The predominant age was 26-45 years old (41.5%). Primary infection (70.7%) was greater than recurrent infection (8.9%) in which recurrence affects 46-65 years old (72.7%). Visual acuity at the initial presentation was <6/18-6/60 (26.2%), and the final follow-up increased to ?6/18 (33.1%). Posterior uveitis (35.1%) with posterior pole lesion (66%) was a common clinical sign found. Medications given were trimethoprim-sulfamethoxazole (51,3%), and corticosteroid (27.5%) as an adjuvant. The complication detected was cataract (13%). Conclusion: Ocular toxoplasmosis was mostly found in immunocompetent male patients, acquired, unilateral, and in the posterior pole. A good response was found by trimethoprim-sulfamethoxazole and corticosteroid medications.